The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2021
DOI: 10.1021/acs.iecr.1c03661
|View full text |Cite
|
Sign up to set email alerts
|

Computer-Aided Design of a Perfluorinated Sulfonic Acid Proton Exchange Membrane Using Stochastic Optimization and Molecular Dynamic Method

Abstract: In this paper, a computer-aided polymer design (CAPD) framework with a stochastic optimization model is proposed for the design of perfluorinated sulfonic acid proton exchange membrane (PFSA-PEM) with desired properties. First, the requirements and target characteristics are identified and converted to property constraints. Then, the polymer design model is formulated as a stochastic optimization problem in which the operation temperature is treated as a random variable. Subsequently, the formulated stochastic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
7
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4
1

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(7 citation statements)
references
References 50 publications
0
7
0
Order By: Relevance
“…The aided design algorithm described in this study is also contrasted with the classic aided design algorithm. In Reference [ 25 ], the design similarity index is used to calculate the measurement index. Figure 5 depicts a comparison diagram of the two options.…”
Section: Simulation Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…The aided design algorithm described in this study is also contrasted with the classic aided design algorithm. In Reference [ 25 ], the design similarity index is used to calculate the measurement index. Figure 5 depicts a comparison diagram of the two options.…”
Section: Simulation Resultsmentioning
confidence: 99%
“…Scene visual understanding is one of the most widely utilized computer technologies in the field of the art design, and it is one of the most widely integrated computer technologies in the field of art design [ 24 , 25 ]. Aiming to replace the human eye and brain with computers, scene vision understanding is the process of using computers to simulate the visual function of the human eye and brain to perceive, recognize, and understand three-dimensional scenes and objects in the objective world, as well as to analyze complex objects in scene images by integrating with natural language.…”
Section: Introductionmentioning
confidence: 99%
“…Liang et al [5] proposed a computer-aided polymer design (CAPD) framework for the design of rubber tires. Guo et al [6] developed a CAPD framework with stochastic optimization algorithm, which is used for the design of perfluoro sulfonic acid proton exchange membranes (PEM). However, only the effects of repeating unit structure, molecular weight and side chain structure distribution of polymer on the properties were considered in previous work, the effect of crosslinking was ignored.…”
Section: Introductionmentioning
confidence: 99%
“…Recent research has demonstrated that it is possible to target specific properties and design compound, which will produce a membrane with those properties using CAMD [11]. Artificial neural networks (ANNs), which define a branch of machine learning, are capable of discovering complex patterns from large datasets.…”
Section: Introductionmentioning
confidence: 99%
“…Artificial neural networks (ANNs), which define a branch of machine learning, are capable of discovering complex patterns from large datasets. Applying the predictive power of ANNs to CAMD, specifically to predicting the properties of membrane polymers, provides reasonable results at a fraction of the computational cost of rigorous simulations [11,12], and avoids the costly and unfocused guess-and-experiment approach. This makes it possible to consider new membrane polymers on a scale which is orders of magnitude larger than either rigorous simulations or guess-and-experiment approaches would allow.…”
Section: Introductionmentioning
confidence: 99%